Arthroscopic release and labral repair for bifocal compression of the suprascapular nerve - Radic, Ross R. (Shoulder Elbow, 2015)
We present a rare case of combined proximal and distal compression of the suprascapular nerve causing supra- and infraspinatus weakness and wasting in a 17-year-old rower. Clinical findings, magnetic resonance imaging and electromyeographic studies confirm this. The case was managed with an arthroscopic approach, consisting of arthroscopic labral repair and decompression of a paralabral cyst, combined with arthroscopic release of the transverse scapular ligament. An excellent result was achieved, with the patient returning to full competitive rowing prior to the 6-month clinical review. This case highlights the interesting nature of bifocal compression of the suprascapular nerve, as well as the successful use of arthroscopic techniques to manage the problem.